Systemic Liquidity Management in the U.A.E. : Issues and Options - Chailloux, Alexandre (IMF Working Papers; Working Paper, 2009)
The paper analyzes the U.A.E.'s liquidity management framework in the context of the 2008 global financial crisis and the measures taken by the Central Bank of the U.A.E. to ease liquidity pressures in the second half of 2008. Drawing also on an empirical analysis of data for 15 U.A.E. banks through end-2008, the paper emphasizes the importance of making available to banks additional instruments to manage their liquidity as well as to strengthen the monitoring of a more comprehensive set of liquidity risk indicators. As regards the former, the paper discusses the merits and scope for the U.A.E. to introduce a domestic bond market.